In Vitro Propagation of Buah Merah (Pandanus Conoideus Lam) Through Lateral Bud Proliferation - Imelda, Maria; Wulansari, Aida; Sumarnie, Sumarnie (ANNALES BOGORIENSES, 2008)
Pandanus  conoideus Lam  or  Buah  merah  of the  Pandanaceae  is  native  to  East  Indonesia,  particularly Papua and  North Maluku. Traditionally  the  fruits  are  used  for health  promotion and maintenance as well  as  for curing  several  illnesses.  Recently,  it  has  been  reported  that  the  fruits  are  potential  for  cancer medication . As a result, there  has  been  an  overexploitation of the  plants  from  their habitats .  In  order  to  anticipate  their possible disappearance due to overexploitation in the wild, an efficient and effective technology for the mass propagation, conservation and  cultivation  of these plants should be developed. Generally  buah merah is propagated vegetatively by  offshoots and stem cuttings or generatively by seeds.  Micropropagation  has  many  advantages  over  the conventional method. because  the  technique allows mass  cIonal  and  pathogen-free  production of plants  at high  rate of multiplication all  year round . In  this  research the  effects of 0,1 -0.2 mg/l thidiazuron  (TDZ), 0.5- 1.0 benzyl  amino  purine  (BAP)  and  0.25-0.5  mg/l  Kinetin  (KN)  on  shoot  bud  induction  and  proliferation of P.  conoideus were  investigated  using  nodal   sections  or  lateral buds  or P.  conoideus  on modified  Murashige and skoog medium. Shoots were rooted on MS medium  without plant growth  regulators (PGR) . The  result  showed that  lateral  buds  of Pandanus  started  to  initiate  growth after 4-7  days  in  culture.  The  best medium  for  shoot proliferation  was MS  containing either 0,5 mg/l  BAP with  0.1 mg/ l  TDZ or  I  mg/l  BAP with  0.5  mg/I  KN. giving a multiplication rate of  I6.5  shootlets per shootbud explant after 8 weeks Rooting of shoots was successfully conducted on MS medium without PGR.  Acclimatization of  rooted plantlets was achieved on  a mixed medium of  cocopeat and soil (1:1). Keywords: Buah merah (Pandanus conoideus). lateral buds, BAP. TDZ. KN